2018
DOI: 10.1038/s41585-018-0055-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of BCG immunotherapy and its outlook for bladder cancer

Abstract: BCG immunotherapy is the gold-standard treatment for non-muscle-invasive bladder cancer at high risk of recurrence or progression. Preclinical and clinical studies have revealed that a robust inflammatory response to BCG involves several steps: attachment of BCG; internalization of BCG into resident immune cells, normal cells, and tumour urothelial cells; BCG-mediated induction of innate immunity, which is orchestrated by a cellular and cytokine milieu; and BCG-mediated initiation of tumour-specific immunity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
275
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 347 publications
(284 citation statements)
references
References 148 publications
2
275
1
6
Order By: Relevance
“…In a mouse model study, depletion of neutrophils abolished the therapeutic effect of BCG by diminishing monocyte and CD4+ T cell infiltration in the bladder . However, it is yet to be verified if neutrophils are essential in BCG‐induced immunity in human bladder cancer . In a mouse model, depletion of NK cells also reduced efficacy of BCG immunotherapy .…”
Section: Mechanisms Of the Response Of Nmibc To Bcg Immunotherapymentioning
confidence: 99%
See 4 more Smart Citations
“…In a mouse model study, depletion of neutrophils abolished the therapeutic effect of BCG by diminishing monocyte and CD4+ T cell infiltration in the bladder . However, it is yet to be verified if neutrophils are essential in BCG‐induced immunity in human bladder cancer . In a mouse model, depletion of NK cells also reduced efficacy of BCG immunotherapy .…”
Section: Mechanisms Of the Response Of Nmibc To Bcg Immunotherapymentioning
confidence: 99%
“…Another 5‐year follow‐up study of 262 patients, also demonstrated that intravesical BCG significantly prevented recurrence compared to doxorubicin (63% versus 87% recurrence rate) . In 1990, the FDA approved intravesical instillation of BCG for NMIBC treatment, which was considered as a breakthrough cancer therapy .…”
Section: The Success Of Bcg Intravesical Instillations For Early‐stagmentioning
confidence: 99%
See 3 more Smart Citations